Relation between response to exercise and diurnal variability of peak expiratory flow in primary school children. Issue 3 (March 1993) - Frischer, T; Kühr, J; Meinert, R; Karmaus, W; Forster, J; Urbanek, R
Abstract : BACKGROUND: Variability in peak expiratory flow (PEF) has been proposed as a simple method of screening for asthma in epidemiological studies. This study was designed to assess whether the bronchial response to exercise and the diurnal variation in PEF identified the same subjects. METHODS: Bronchial response to a free running exercise test was assessed in a cohort of 918 seven year old children and was compared with variability of PEF as assessed by twice daily recordings for a one week period. Mini Wright peak flow meters were used throughout the study. RESULTS: Baseline PEFs of both tests were highly correlated but there was no significant correlation between a response to exercise and variability of PEF. Of 33 children with a physician's diagnosis of asthma, 18 had at least one abnormal test, but only five children were abnormal in both tests, showing that the tests did not identify the same subjects. CONCLUSION: Increased variability of PEF, as well as a response to exercise, was associated with respiratory symptoms, but only a response to exercise was closely associated with atopy (defined as a positive skin test to any of seven aero-allergens).